Studies on heavy metal contaminantion of water and sediment from Pahang River, Pahang, Malaysia - Zaharudin, Nazikussabah; Muhammad, Amin; Misni, F. (2011)
A study was conducted in order to determined heavy metal concentration in water and sediment at selected sites of Sg. Pahang, Pekan, Pahang (Pahang River). A total of three monitoring stations were established along Sg. Pahang. Three selected sampling point is located near Kampung Batu Sawar, Kampung Padang Rambia and Taman Merdeka, Pahang. Samplings were conducted seven times over a period of seven months from March 2010 to September 2010. Concentrations of heavy metals such as Zinc (Zn), Plumbum (Pb ), Copper (Cu) and Cadmium (Cd) were determined. The results were then compared with the Interim National Water Quality Standards for Malaysia (INWQS). In determination of heavy metals, water and sediment samples were analysed using Atomic Absorption Spectrophotometer (AAS). Results of this study indicated that Sg. Pahang is classified into Class I -Class II base on (INWQS). The trend of heavy metals in water and sediments of Sg. Pahang is Zn> Pb> Cu> Cd. All heavy metals were detected at low concentartion in water and sediment samples. The concentrations of heavy metals in the river water ranged between Zn, (15.22 - 52.91) µg/L.; Pb, (2.75- 12.38); µg/L. Cu, (2.79- 9.92) µg/L.; Cd, (0.16- 0.37) µg/L and the concentrations of heavy metals in sediment ranged between Zn, (20.92- 189.34) µg/g.; Pb, (8.91 - 38.52) µg/g.; Cu, (3.83 - 26.54) µg/g. It was found that the concentration for metals increased as the river water flow from Kampung Batu Sawar to Taman Merdeka. This may be due to agricultural activities, sand mining, fishing activities, sea dumping and industrial development near Pekan. Generally, the concentrations of heavy metals were relatively low and it can be concluded that the river status is clean and under Class II.